Redactable blockchain with anonymity and multi-permission for instructional management - Xiuhua Lu; Jing Liu; Fengyin Li; Jiazheng Zou; Yuhao Hou (Blockchain: Research and Applications)
An instructional management system (IMS) regularly manages student data with a centralized database, which may be prone to single points of failure and data tampering. Blockchain can effectively solve the above problems due to its decentralization and immutability. However, the immutability of blockchain restricts the edit of data in some cases (e.g., incorrect score records). In this paper, we propose an advanced decentralized instructional management framework based on redactable blockchain, wherein chain nodes possess the capability to autonomously revise their initiated transactions with regular chameleon hash functions. Concurrently, system users can anonymously report discrepancies or erroneous entries within the blockchain. When such reports are validated and malicious activities are confirmed, the review team can undertake decentralized modifications to rectify the malicious content with our proposed scheme. In addition, we conduct a security analysis of the scheme, evaluating its correctness, collision resistance, and claimability. Finally, experimental results demonstrate that the scheme is practical.